DIVERSITY OF FRUIT FLIES (DIPTERA: TEPHRITIDAE) ATTRACTED BY ME LURE IN CSC-BG GERMPLASM CARAMBOLA PLANTATION - Riastiwi, Indira; Paradisa, Yashanti Berlinda; Mambrasar, Yasper Michael; Raunsai, Marlin Megalestin; Perwitasari, Urip; Volkandari, Slamet Diah; Sari, Nurul Fitri; Sulistiyani, Tri Ratna; Ibo, Leberina Kristina (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2021)
Diversity of fruit flies (Diptera: tephritidae) attracted by me lure in CSG-BG germplasm carambolae plantation. Germplasm Garden (KPN) Cibinong Science Center-Botanical Garden (CSC-BG) is one of the gardens that conserve and utilizes Indonesian local germplasm, one of which is carambolae. The current problem in KPN is the attack of fruit flies (Bactrocera spp.). This study was conducted to determine the diversity of fruit flies in the KPN carambola plantation area. A total of eight traps were placed randomly in the plantation area. Each trap contained 1 mL of methyl eugenol pheromone solution. Identification of fruit flies was carried out based on three morphological differences, they were wings, abdomen, and hind legs. There were 317 fruit flies collected and separated into three species, namely Bactrocera carambolae, B. papayae, dan B. umbrosa, of which B. carambolae had a dominance index of 0.74 and abundance index of 85%. Data on the types of fruit flies can be used as primary data to determine the preparation of pest prevention efforts.